Recovering the tidal field in the projected galaxy distribution. Issue 1 (21st April 2016) - Alonso, David; Hadzhiyska, Boryana; Strauss, Michael A.
Abstract: We present a method to recover and study the projected gravitational tidal forces from a galaxy survey containing little or no redshift information. The method and the physical interpretation of the recovered tidal maps as a tracer of the cosmic web are described in detail. We first apply the method to a simulated galaxy survey and study the accuracy with which the cosmic web can be recovered in the presence of different observational effects, showing that the projected tidal field can be estimated with reasonable precision over large regions of the sky. We then apply our method to the Two Micron All-Sky survey and present a publicly available full-sky map of the projected tidal forces in the local Universe. As an example of an application of these data, we further study the distribution of galaxy luminosities across the different elements of the cosmic web, finding that, while more luminous objects are found preferentially in the most dense environments, there is no further segregation by tidal environment.